LETTER AND POLYPHONIC SPEECH IN HISTORICAL TETRALOGY - Yakhshieva, Zebo; Yakhshieva, Zebo; Daminov, Akmal (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses the role of the genre of writing aimed at ensuring the poetic integrity of fiction. In the artistic composition “The Great Reign” of Mohammed Ali, the writing genre occupies a special place. In this case, the edges of the character were determined. Mironshah Mirzo was dedicated to the essence of the disease of glory that occurred in his nature. A talented writer, historian, translator and publicist, acquainted with the work of Muhammad Ali, cannot forget that he also enjoyed his own poetry. This is because in every object created by the poet, there is strong lyricism, drama, philosophical and aesthetic integrity. In particular, not only the author’s desire to create a polyphonic novel, but also it can be explored by rethinking it from the depths of the text. One of the supporting elements in coordinating the plot and composition of a work of art is writing.